2022
DOI: 10.1167/tvst.11.3.38
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Incomplete Blinking Analyzed Using a Deep Learning Model With the Keratograph 5M in Dry Eye Disease

Abstract: Purpose To establish a deep learning model (DLM) for blink analysis, and investigate whether blink video frame sampling rate influences the accuracy of analysis. Methods This case-controlled study recruited 50 dry eye disease (DED) participants and 50 normal subjects. Blink videos recorded by a Keratograph 5M, symptom questionnaires, and ocular surface assessments were collected. After processing the blink images as datasets, further training and evaluation of DLM was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Aside from looking at the ocular surface imaging modalities, other important predictors of DED such as blinking patterns like incomplete blinking was also explored [ 57 , 58 ]. In a study of 100 patients (50 with DED and 50 with healthy eyes) by Zheng et al, blink videos were recorded using Keratography 5 M (K5M; Oculus Optikgeräte GmbH, Wetzlar, Germany) [ 59 ]. A U-Net model was then used to extract 30 frames per second (FPS) white light videos, and 8 FPS infrared light videos, which were then utilised to derive blink profiles.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from looking at the ocular surface imaging modalities, other important predictors of DED such as blinking patterns like incomplete blinking was also explored [ 57 , 58 ]. In a study of 100 patients (50 with DED and 50 with healthy eyes) by Zheng et al, blink videos were recorded using Keratography 5 M (K5M; Oculus Optikgeräte GmbH, Wetzlar, Germany) [ 59 ]. A U-Net model was then used to extract 30 frames per second (FPS) white light videos, and 8 FPS infrared light videos, which were then utilised to derive blink profiles.…”
Section: Main Textmentioning
confidence: 99%
“…A U-Net model was then used to extract 30 frames per second (FPS) white light videos, and 8 FPS infrared light videos, which were then utilised to derive blink profiles. It was found that blink videos with 30 FPS have higher accuracy in detecting incomplete blinking which was a sensitive indicator of DED [ 59 ]. Another important predictive factor of DED is meibomian gland dysfunction (MGD) which results in the disruption of the tear film lipid layer and increases the tear film evaporation rate [ 60 ].…”
Section: Main Textmentioning
confidence: 99%
“…Through AI analysis, Jing et al (2022) have found a significant correlation between corneal nerve morphological changes in patients with dry eyes and intrinsic corneal aberrations, particularly higher-order aberrations. Zheng et al (2022) established a blink analysis model using AI to generate a blink profile, which provides a new method for evaluating incomplete blinking and diagnosing dry eye. The above research shows that the AI model has achieved remarkable results in the segmentation of MG morphology in patients with dry eye.…”
Section: Figurementioning
confidence: 99%
“…These methods enabled the accurate detection and quantitative measurement of the dry areas, which can be helpful for the evaluation of the severity of DED [ 71 , 72 ]. Recently, Zheng et al [ 73 ] developed a DL-based algorithm for blink analysis using videos recorded by a Keratograph ® 5M (Oculus Optikgeräte GmbH, Wetzlar, Germany). In this study, the frequency of the incomplete blinking measured using the AI model was closely associated with the signs and symptoms of DED, suggesting the potential of the DL algorithm as a diagnostic tool for DED [ 73 ].…”
Section: Application Of Ai In Diagnosis and Treatment Of Dedmentioning
confidence: 99%